Characteristics of analytically confirmed illicit substance-using patients in the Emergency Department - Te-I Weng; Lian-Yu Chen; Ju-Yu Chen; Pai-Shan Chen; Hsaio-Lin Hwa; Cheng-Chung Fang (Journal of the Formosan Medical Association, 2020)
Background/Purpose: Although illicit substance use-induced toxicity or complication is a frequent cause of visit to the emergency department (ED), there are limited data on cases confirmed by liquid chromatography tandem-mass spectrometry (LC-MS/MS) analysis. This study aimed to describe clinical presentations of patients who visited the ED because of acute illicit substance-related complications. Methods: We performed a retrospective study between May 2017 and August 2018 on patients presenting to the ED with positive urine illicit substance analysis by LC-MS/MS. Results: Of 203 patients with at least one illicit substance detected in their urine, 162 (79.8%) showed traditional illicit substances, and 56 (32.0%) showed new psychoactive substances (NPS). Methamphetamine was the most common illicit substance (67.9%). The most common NPS was ketamine (21.7%), followed by synthetic cathinones (14.8%). We divided patients into traditional, NPS and combined (both traditional illicit substance and NPS) groups. Polysubstance use was more common in the NPS group than in the traditional group (P < 0.001). Most patients were men (78.3%), and the average age was lower in the NPS group compared to the traditional group (P < 0.001). Although the chemical structures of cathinones are similar to that of amphetamine, 92.0% of the cathinone use cases without combination with methamphetamine use showed negative immunoassay results. Conclusion: Our study provided the acute illicit substance complications at ED by LC-MS/MS analysis in Taiwan. Our study showed that more than one-third cases studied were NPS users. Young adults and polysubstance users were more common among NPS users.